The Nature of Basic Human Potential ('Aql, Nafs, and Qalb) and its Relevance With Islamic Education - Ahmad Zaki Annafiri; Sulthon Abdul Aziz (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2022)
The discourse on human history never ends, because it is a perfect creation and full of uniqueness. Human nature is difficult to study because every time the discussion is over, there are still other interesting themes to discuss. The background of this paper is the need for efforts to explore the nature of basic human potential as a way of ta'abbudi, and find ways to develop it through Islamic education, a process that was started by the Prophet Muhammad several centuries ago. This research is a descriptive qualitative research based on literature review, describing the basic human potential from a philosophical perspective and its development through Islamic education. The primary source in this study is the Book of Fiqhun Nafs by Yahya bin Ibrahim, as well as secondary sources in the form of books, articles, and related scientific works. The results of this study are 1) the dimensions of human nature that must be directed to monotheism by Islamic education in order to be safe from deviations in aqidah, 2) Islamic education efforts to keep the nafs al-muthmainnah in its position, and direct the nafs al-lawwamah to have a tendency to kindness, and diverting the nafs al-Ammarah to leave its position, 3) reflecting on and reflecting on the vast creation of Allah SWT as an effort to direct the human mind to always be used for goodness, and return to revelation when encountering obstacles in reaching conclusions, 4) imitating the Prophet Muhammad in being gentle and compassionate as an Islamic education effort in directing the heart towards perfecting morals which is the main goal of the Messenger of Allah sent.